1996
DOI: 10.21273/jashs.121.6.1157
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Chemical Changes during Ripening of Costa Rican Bananas Harvested in Different Seasons

Abstract: Mature green `Grande Naine' bananas (Musa AAA) were harvested 13 weeks after flowering in June and Sept. 1993 and Feb. and Mar. 1994 and were sent air freight to Raleigh, N.C. Fruit were held under 1) storage (36 days at 14 C and 80% to 90% relative humidity) or 2) ripening (8 days storage, followed by ethylene treatment on day 8 and subsequent storage at 17 °C and 80% to 90% relative humidity). Despite of similar grade and age, length of the preclimacteric phase (green life)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…As banana ripen, a series of physiological and chemical changes occur such as the reduction in fresh weight, starch content, peel colour, fruit firmness, soluble solids concentration and organic acid percentage (Marin et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…As banana ripen, a series of physiological and chemical changes occur such as the reduction in fresh weight, starch content, peel colour, fruit firmness, soluble solids concentration and organic acid percentage (Marin et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…In bananas at a more mature stage, flesh firmness and starch content decrease whereas total sugars content and titratable acidity increase (Abdullah et ul. 1985;Munasque et al 1990). When harvested banana fruits are treated with ethylene, changes in flesh firmness and starch content occur at a rapid rate (Marin et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…1985;Munasque et al 1990). When harvested banana fruits are treated with ethylene, changes in flesh firmness and starch content occur at a rapid rate (Marin et al 1996). That information is consistent with ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marin et al. (1996) reported that banana harvesting date has been based on either making a direct measure of fruit characteristics, such as the diameter of a finger on a bunch, or more simply the fruit age in number of weeks after flowering for many years. Cavendish bananas (AAA) are required to have a minimum diameter of 32 mm before being suitable for harvest and export, while ‘Goldfinger’ (AAAB) can be harvested at 36−39 mm (Brat et al., 2020).…”
Section: The Banana and Plantain Industrymentioning
confidence: 99%